Patterns of Injury in Homicide Relationships: Clinical, Psychological, and Investigative Implications - Alvarez Cussen, Shea L (2017)
Despite accounting for only 1.3% of all violent crime, homicide still, perhaps more than ever, garners widespread fascination. It has long been recognized as a complex event characterized by variations in behavioral style, level of violence, motivation, and personal interaction. Mixed findings and methodological variation (i.e., lack of standardized method of measuring injury severity, sampling bias, varying definitions of victim-offender relationships) regarding severity of wounding and victim-offender relationship highlight the need for more empirical research. The importance of considering multiple elements of a crime when attempting to obtain a psychological understanding of victim-offender dynamics has been neglected. In an effort to respond to these shortcomings, the current study employed a series of multinomial logistic regressions to examine various demographic and offense characteristics across a nonrandom, national U.S. sample of 242 homicide cases reflecting a variety of homicide subtypes and victim-offender relationships. Findings support the assertion that severe facial wounding is associated with more intimate relationships. While additional findings suggest that variations in wounding do indeed exist between relationships and homicide types, caution should be taken by investigators due to nuanced differences related to frequency and severity of wounds